Analisis Pelayanan Pusat Kesehatan Masyarakat (PUSKESMAS) Panca Berdasarkan Prinsip Service Excellent - Malik Abdul Aziz; Maman Suryaman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Community health centers (Puskesmas) have become one of the people's choices for treatment, medical examinations and so on. Panca Health Center is one of the Community Health Centers in Nagrak Village, District. Pacet, Bandung Regency, is an option for the people there who want to have a health check. Community health centers (Puskesmas) play an important role in providing primary health services for the community. In an effort to improve service quality, the application of the principle of excellent service is crucial. Service excellence is an approach that prioritizes customer satisfaction through providing services that exceed expectations. This research aims to evaluate the implementation of excellent service principles in Community Health Centers, focusing on aspects such as responsiveness, reliability, assurance, empathy and physical evidence. The research method used was a case study at the Community Health Center in Panca. Data was collected through interviews, interviews and direct observation. The research results show that Community Health Centers that apply the principle of excellent service are able to increase patient satisfaction, speed up response time, and improve the quality of communication between health workers and patients. In addition, factors such as continuous training for staff, improving physical facilities, and implementing a health information system also contribute to achieving service excellence. Researchers can conclude that implementing the principle of excellent service in Community Health Centers not only improves service quality, but also strengthens public trust in primary health services. Recommendations are provided to expand the application of these principles to achieve higher standards of health care on an equitable basis.